Local Channels under Decomposition of Quantum Gates in Bipartite Systems - Yihui Lao; Pei Wang; Shanli Liao (Journal of Mathematics)
For a bipartite quantum system with Hilbert space Hm⊗Hn, this paper considers a quantum channel ϕ from the system to itself which preserves the set of separable states. Within this class of quantum channels, the paper characterizes those channels which preserve the Tsallis entropy of combinations of separable states through decomposing quantum gates, where the characterization is given in terms of the action of the channel on separable states.